Implementasi Fuzzy Inference System untuk Pengstabilan Arus pada Baterai Lithium di Electric Vehicle - Arizal Mujibtamala Nanda Imron; Satryo Budi Utomo; Dimas Aldy Darmawan; Bambang Sri Kaloko; Zilvanhisna Emka Fitri (LPPM, 2025)
The application of renewable energy in electric vehicles (EVs) is a crucial aspect that requires careful consideration. It is essential to understand the capacity characteristics of lithium polymer batteries to develop effective testing procedures. These procedures should involve monitoring the battery's voltage, current, and temperature during the discharge process with a lamp loading of 5 watts. The results of research prove that fuzzy control is an effective method for minimising the increase in battery temperature by stabilising the current used by the battery. The fuzzy control system effectively regulated a battery with a capacity of 3300 mAh and a voltage of 11.1 Volts, maintaining a stable current of 0.3 A from the 3rd minute until the battery reached its maximum capacity at the 63rd minute. Furthermore, the implementation of fuzzy control has been observed to delay the temperature rise in the battery. Specifically, the use of fuzzy control enables a delay in the temperature rise time by approximately 14 minutes when compared to the system without control. The temperature rise has a significant impact on the discharge speed of lithium polymer batteries.